Optimized Production of Xylanase by Penicillium purpurogenum and Ultrasound Impact on Enzyme Kinetics for the Production of Monomeric Sugars From Pretreated Corn Cobs - Sunkar, Bindu; Kannoju, Balakrishna; Bhukya, Bhima (Frontiers in Microbiology, 2020)
Corn cob is one of the abundant organic sources envisioned for the development of biorefineries. For the effective conversion of the feedstocks to valued commodities, effective biocatalysts are highly desired. The present study aims at optimizing the critical parameters required for xylanase production by Penicillium purpurogenum isolated from the rotten wood sample using the Taguchi orthogonal array layout of L25 (5˄6). The optimized conditions like temperature 40 ⁰C, pH 3, size of inoculum 1.2X108 spores/ml, moisture 70%, peptone 0.8%, and 5 days of incubation resulted in 1060 ± 30.0 U/gds xylanase which was 64.52% more when compared to un-optimized production of xylanase i.e. 247.23 ± 30.45 U/gds. The xylanase thus produced could effectively promote pretreated corn cob saccharification and the reaction was further intensified with ultrasound assistance which has increased the saccharification to 12% by producing 209.67 ± 8.08 mg/g xylose. The saccharification efficiency of pre-treated corn cob was found to be 80.29% more compared to the raw corn cob reflecting its recalcitrance to digestion. Indeed, xylan being the second most abundant, considerable attention is being paid for its effective conversion to valued asset.